2015
DOI: 10.1093/jxb/erv330
|View full text |Cite
|
Sign up to set email alerts
|

The co-chaperone p23 controls root development through the modulation of auxin distribution in theArabidopsisroot meristem

Abstract: Statementp23 co-chaperones play a key role in the root meristem maintenance via regulation of auxin signalling and the consequent balance between cell differentiation and division rate at the transition zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…It is well known that the activity of the RAM determines root growth (Grunewald et al, 2012 ; Perilli et al, 2012 ; Petricka et al, 2012 ; D'alessandro et al, 2015 ). To investigate whether the growth inhibition of soybean roots by salt is due to a reduction in root meristem activity, we measured the length of the meristem zone in longitudinally cut root tips from seedlings grown in 0 or 75 mM NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the activity of the RAM determines root growth (Grunewald et al, 2012 ; Perilli et al, 2012 ; Petricka et al, 2012 ; D'alessandro et al, 2015 ). To investigate whether the growth inhibition of soybean roots by salt is due to a reduction in root meristem activity, we measured the length of the meristem zone in longitudinally cut root tips from seedlings grown in 0 or 75 mM NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…HOP isoforms are represented by three genes . p23 proteins are encoded by two genes in Arabidopsis , while AT3G12050 represents the Arabidopsis homolog to Activator of HSP90 ATPase (Aha1). Aha1 is a HSP90 co‐chaperone that binds to the N‐terminal HSP90 domain and inversely to p23 positively regulates HSP90 ATPase activity but has so far not been characterized in plants.…”
Section: Hsp90 Co‐chaperones In Arabidopsismentioning
confidence: 99%
“…Mutants of the two isoforms of the Arabidopsis homolog to mammalian p23 exhibit altered auxin distribution patterns in the root tip and delocalization as well as transcriptional repression of PIN proteins. This may explain a short root phenotype, shorter meristem length and reduced cell number in the division zone and implies p23 isoforms as regulators of PAT . Moreover, the Arabidopsis TPR‐immunophilin FKBP42, twisted dwarf 1 (TWD1), was shown to interact with HSP90 both in vitro and in vivo .…”
Section: Roles Of Hsp90 and Its Co‐chaperones In Hormone Biologymentioning
confidence: 99%
“… Löfke et al (2015) characterize the relative contributions of PIN2 auxin efflux carrier activity in atrichoblasts and root hair cell files. The role of chaperone proteins in maintaining auxin flows is expanded by a study from D’Alessandro et al (2015) in which the p23 chaperone protein is shown to regulate auxin-dependent root development and meristem function. Song et al (2015) characterize interactions between cytokinin biosynthetic genes and nutrient mobilization proteins in Brassica napus development.…”
mentioning
confidence: 99%